Handling Disputes In Murabahah Agreements By Litigation - Hasanuddin .; St. Rajiah Rusidy; Reski Adi (JOURNAL OF SHARIA ECONOMICS, 2023)
This research aims to evaluate the level of readiness of judges in dealing with sharia economic cases, especially in the context of litigation at the Makassar Religious Court. Within this framework, this research identifies two options that can be used to resolve economic disputes involving sharia law before entering the litigation process: the peaceful settlement option through negotiations outside the court (non-controversial) and the settlement option through litigation in court. However, the use of litigation to resolve economic cases involving sharia law in the Makassar Religious Court is still relatively low. This research uses a qualitative description method by collecting data through document study and interviews with stakeholders of the Makassar Class 1A Religious Court. In its implementation, it was found that the judges at the Makassar Class 1A Religious Court were not fully prepared to handle cases related to sharia economics, both in simple trials and ordinary trials. This is due to the small number of sharia economic cases submitted to court as well as the lack of training and certification of judges in the field of Islamic economics. The results of this research emphasize the importance of increasing the readiness of judges in handling sharia economic cases, including efforts to increase training and certification in this field. In addition, this research also highlights the importance of encouraging amicable resolution before engaging in litigation to reduce the burden on courts and facilitate faster and more efficient dispute resolution.